Text availability and the speaker's visibility in simultaneous interpreting: effects on the process, product, and interpreters' perceptions. - Peng, Xuejiao; Wang, Xiangling; Chen, Guangjiao (Perspectives: Studies in Translatology, 2026)
The input condition in simultaneous interpreting (SI) varies in practice, yet the effects of different input modalities on SI still remain largely unknown. To that end, text availability and the speaker's visibility, two typical sources of multimodal input, were chosen to explore the effects of input modality on the SI process (fluency), product (accuracy), and interpreters' perceptions. Data were collected from thirty student interpreters performing four comparable speeches from English to Chinese in four different conditions: audio-only, audio-video (speaker visible), audio-text (verbatim text available), and audio-video-text (speaker visible and verbatim text available). The results from analyzing audio recordings, questionnaires, and interview data showed that the increase in redundant information did not deteriorate the interpreting fluency and accuracy. Input modality had a significant effect on SI, with text availability significantly facilitating source language comprehension and target language production at the global level. However, text availability also introduced challenges in ear-eye-voice coordination at the local level. Additionally, the speaker's visibility performed a supplementary function by promoting engagement and providing paralinguistic cues that facilitate communication. Individual differences existed in interpreters' perceptions under different input conditions, with different challenges reported. These findings expand our understandings of multimodal processing in SI.